Hibridisasi Algoritme Genetika dan Simulated Annealing untuk Optimasi Multi-Trip Vehicle Routing Problem with Time Windows (Studi Kasus: Pariwisata Kabupaten Banyuwangi) - Amalia Kartika Ariyani; Wayan Firdaus Mahmudy (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Along with the rapidly excalation in the number of tourists as well as tourism which are located in Banyuwangi, problems arise from the tourists. With limited time, they would like to visit as many destinations without wasting time in traveling. However, another problem happened when the visitor and each visited destination has time windows or visiting time which has been established. From this issue, it needs a solution to solve the problems regarding with the tourism scheduling with the optimal time based on time windows from the tourists and the destinations. Generally, these problems called Vehicle Routing Problem with Time Windows (VRPTW). VRPTW problems can be solved with several optimization methods, including using hybridizing genetic algorithm and simulated annealing. Genetic algorithms (GA) will be used to explore the global optimum problem, while Simulated annealing (SA) will be used to exploit a local optimum problem. The fitness value approach optimal i.e. of 1.0616 obtained by using parameters of GA-SA on the size of population of 400, amount of generation by 800, combination of cr and the mr of 0.3 and 0.1, initial temperature of 0.9, cooling factor of 0.9, and the coefficient of acceptance of a new solution amounting to 200. Using these parameter values hybrid GA and SA outperforms separated GA and SA.